RACIAL DISCRIMINATION IN ERIN GRUWELL’S THE FREEDOM WRITERS DIARY - AULIARANI SIREGAR, DESTY (LANGUAGE HORIZON, 2018)
The Freedom Writers Diary (1999) is an epistolary book that based on a true story of Erin Gruwell and her students in facing racial discrimination and how they fight against it. This study attempts to answer the question: ?How is racial discrimination depicted in Erin Gruwell?s The Freedom Writers Diary?? This study specifically uses the theory of racial discrimination by Fred L. Pincus. The result shows two types of racial discriminations are depicted in the novel; individual discrimination and structural discrimination.